Does Misoprostol for Induction of Labor Increase the Risk of Uterine Rupture? - Kiswa Anggreany; Mohammmad Luthfi; Risanto Siswosudarmo (Fakultas Kedokteran, Kesehatan Masyarakat dan Keperawatan UGM, 2016)
Background: Misoprostol is a synthetic prostaglandin E1 analogue which is now commonly used for induction of labor. Hyperstimulation is a complication of misoprostol that may lead to uterine rupture.Objective: To find the association between misoprostol exposure for induction of labor with uterine rupture.Methods: Case were all women who delivered in Sardjito and affiliate Hospitals from January 2007 to November 2012 with the diagnosis of uterine rupture. Controls were taken randomly from the same hospital. Chi square test and logistic regression model were used for statistical analysis.Result and Discussion: There were 53 cases of uterine rupture and 199 controls. The incidence of uterine rupture was 53 over 64,244 deliveries or 0,08%. Risk of of uterine rupture associated with misoprostol exposure was 1, 09 (CI 95% 0,52-2,2), while that of oxytocin exposure was 0,80 (CI 95% 0,35-1,85). Logistic regression analysis showed that the highest risk factor associated with uterine rupture was fetal weight > 3500 (OR 3,46; 95% CI 1,48-8,56) followed by parity (OR 2,56;95% CI 1,019-6,465) and vacuum extraction(OR 2,45;95% CI 0,94-6,39).Conclusion: There was no association between misoprostol exposure with uterine rupture. Fetal weight> 3500 gram, Parity more than 3, and vacuum extraction increased the risk of uterine rupture associated with misoprostol use.Keywords: Misoprostol, induction of labor, uterine rupture, fetal weight, parity.